ANALISIS KUALITAS PELAYANAN POLI MATA RUMAH SAKIT ISLAM SAKINAH MOJOKERTO - Maitri Anindita (Kompetensi (Competence : Journal of Management Studies), 2017)
The purposes of this study are determine and analyze the level of service quality in eye clinic Sakinah Islamic hospital. The method used in this research is quantitative descriptive. Primary data from 5 servqual dimensions were collected directly by using questionnaires distributed to patients of eye clinic Sakinah Islamic hospital and then conducted gap analysis to know service quality between patient expectations and reality. The results indicate the patient's expectation on the service quality for tangible, reliability, responsiveness, assurance and empathy dimension is highly expected criteria, while the patient's assessment of the current service condition on the five dimensions of service quality comes in on the very good criteria. There are some gaps with negative scores between the patient's assessment of the current and expected health care service.